2023
DOI: 10.1542/peds.2022-059688
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Central Line Maintenance Bundle and Infection Rates

Abstract: BACKGROUND: Reliable bundle performance is the mainstay of central line-associated bloodstream infections (CLABSI) prevention despite an unclear relationship between bundle reliability and outcomes. Our primary objective was to evaluate the correlation between reported bundle compliance and CLABSI rate in the Solutions for Patient Safety network. The secondary objective was to identify which hospital and process factors impact this correlation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Perhaps information obtained from audits of CLABSI prevention bundle compliance should be used to drive this education. A recent review of 10 years of data from a hospital system found a significant negative correlation between CLABSI prevention bundle compliance and CLABSI rates ( P < .001) 14…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps information obtained from audits of CLABSI prevention bundle compliance should be used to drive this education. A recent review of 10 years of data from a hospital system found a significant negative correlation between CLABSI prevention bundle compliance and CLABSI rates ( P < .001) 14…”
Section: Discussionmentioning
confidence: 99%